2015
DOI: 10.1016/j.palaeo.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Cruziana- and Rusophycus-like traces of recent Sparidae fish in the estuary of the Piedras River (Lepe, Huelva, SW Spain)

Abstract: Modern fish are able to produce a plethora of different traces (both bioturbation and bioerosion structures) according to several behaviours, yet only five ichnotaxa have been interpreted as produced by the activity of fish in the fossil record. Many taphonomic factors may favour the non-fossilization of many of these traces and, even fossilized, they could have been misinterpreted.In this contribution, shallow and bilobed traces produced by the feeding activity of the perciform fish Diplodus vulgaris (Sparida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Recent neoichnological observations ( 27 ) demonstrate that such bilobed biogenic sedimentary structures correspond to feeding trails produced by fishes that scratch the seafloor with their teeth in search for food. Further evidence for the piscine origin of the trace fossils is shown by the similarity with experimental feeding trails of Holocephali ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent neoichnological observations ( 27 ) demonstrate that such bilobed biogenic sedimentary structures correspond to feeding trails produced by fishes that scratch the seafloor with their teeth in search for food. Further evidence for the piscine origin of the trace fossils is shown by the similarity with experimental feeding trails of Holocephali ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, each lobe of the fossil trail corresponds to the groove produced by the upper incisor-like teeth located on each of the two premaxillae; the central separation between lobes corresponds to sediment flowing through the diastema between the two biggest incisor-like teeth. Modern feeding trails are produced by a front-to-back raking movement during which the sediment is gathered ( 27 ). The bilobed structures studied herein show notably similar characteristics (horizontal orientation, lack of branching, bilobed nature, presence of a central ridge, and centimetric size), and thus, we infer that they have been produced in the same way ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The continental subset includes a review of the application of vertebrate trace fossils to palaeoenvironmental analysis (Melchor, 2015); the role of Permian tetrapod footprints in palaeoenvironmental and palaeoclimatic inferences in an alluvial setting (Marchetti et al, 2015); the contribution of dinosaur ichnology to palaeogeographic reconstructions in complex geodynamic settings (Citton et al, 2015); late Miocene ground sloth footprints from Argentina ; a revision of the ichnotaxonomy of the amazing Pleistocene Pehuen Co mammal and bird footprint site (Aramayo et al, 2015); and behavioral inferences from neoichnological studies on modern vertebrate traces (Dentzien-Dias and Figueiredo, 2015;Muñiz et al, 2015).…”
Section: Continental Ichnologymentioning
confidence: 99%
“…This work yielded intriguing insights into predator avoidance and digging behavior, and demonstrates the utility of burrow architecture for reconstructing ancient environments. Finally, Muñiz et al (2015) enlarge the types of potential fish traces that may be found in the fossil record by analyzing feeding traces of extant fishes in estuarine flats, which roughly resemble the ichnogenera Cruziana and Rusophycos.…”
Section: Continental Ichnologymentioning
confidence: 99%
“…Benthic fishes are known for their diverse tracemaking activity. Examples including resting traces (Seilacher 1953), large predation depressions (Gregory et al 1979), deep, domichnial burrows (e.g., Stanley 1971;Able et al 1987;Boyer et al 1989;Atkinson and Taylor 1991) and shallow feeding depressions (Pearson et al 2007;Muñiz et al 2015) have been described from recent environments. Swimming trails, such as Undichna Anderson, 1976, and feeding traces (e.g., Osculichnus Demírcan and Uchman 2010) occur starting in the Devonian (e.g., Trewin 2000;Soler-Gijón and Moratalla 2001;Szrek et al 2016).…”
Section: Introductionmentioning
confidence: 99%